BEBAN KERJA KARYAWAN LAUNDRY DI GRAND JATRA HOTEL PEKANBARU - Rahma Fauziah; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The purpose of this research was conducted to find out and analyze the workload of laundry employees at the Grand Jatra Hotel Pekanbaru. The sample in this study were laundry employees at the Grand Jatra Hotel Pekanbaru. The sampling technique used was a census sample of 7 people. Data collection techniques in this study used interviews and questionnaires (questionnaire). Data analysis techniques in this study used descriptive data analysis techniques. Based on the results of the research and discussion in this study, it is known that some of the workload variables are in the good category. This is evidenced in the responses of respondents who do not agree with the variable use of working time and targets that must be achieved so that the hotel is expected to add its employees. Keywords: Workload